Multipliers of Dirichlet-Type Subspaces of Weighted Bloch Spaces (Journal of Mathematical Study, 2022)
In this paper, we characterize the multipliers on the intersection of the Dirichlet-type space and the logarithmic Bloch space, and the intersection of the Dirichlet-type space and the logarithmic space of analytic functions of bounded mean oscillation.
Keywords: Multiplier; Carleson measure; Dirichlet-type space; weighted Bloch space.